2003
DOI: 10.1046/j.1395-3907.2003.0151.x
|View full text |Cite
|
Sign up to set email alerts
|

Myopia and natural lighting extremes: risk factors in Finnish army conscripts

Abstract: ABSTRACT.Purpose: To establish whether features of environmental lighting in far northern latitudes might be associated with prevalence of myopia. Methods: Using both questionnaires and military medical examinations, this cross-sectional survey of Finnish conscripts assessed both light exposure and conventional risk factors for myopia. Results: While myopia was not associated with the month of birth, there was a trend towards a higher prevalence of myopia among conscripts living above the Arctic Circle, consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 26 publications
2
31
0
Order By: Relevance
“…Following this review, a number of manuscripts were excluded due to information, including outcome, the exposure of interest or essential data, being omitted. A total of 16 studies were eligible for final inclusion (12)(13)(14)(15)(16)(17)(26)(27)(28)(29)(30)(31)(32)(33)(34). Of these, six were prospective cohort (12,13,15,17,31,32), eight were cross-sectional (14,16,(26)(27)(28)(29)(30)35) and two were case-control studies (33,34).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following this review, a number of manuscripts were excluded due to information, including outcome, the exposure of interest or essential data, being omitted. A total of 16 studies were eligible for final inclusion (12)(13)(14)(15)(16)(17)(26)(27)(28)(29)(30)(31)(32)(33)(34). Of these, six were prospective cohort (12,13,15,17,31,32), eight were cross-sectional (14,16,(26)(27)(28)(29)(30)35) and two were case-control studies (33,34).…”
Section: Methodsmentioning
confidence: 99%
“…The present meta-analysis included 16 studies with 8,393 cases of myopia. The selected studies were from four continents (seven from Asia (14,16,26,28,32,34,35), four from Europe (17,29,31,33), three from the United States (12,13,30) and two from Australia (15,27). All of the studies recruited male and female participants aged ≤31 years.…”
Section: Final Study Inclusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seasonal variations in photoperiod are particularly extreme above the Arctic Circle. However, in a study of Finnish military conscripts (Vannas, Ying et al 2003) no associations between myopia prevalence and birth month, global irradiance at birth month or daily hours of darkness during the birth month were found, although there was a trend towards higher prevalence of myopia among conscripts living above the Arctic Circle.…”
Section: Season Of Birthmentioning
confidence: 85%
“…A multiple-site study in the U.S. reported that myopic children spent fewer hours outdoors (by 1.1 to 1.8 hours) as compared to emmetropic children before and after the onset of myopia (Jones-Jordan et al, 2011), suggesting that long period spent indoors plays an important role in myopia development. Some studies have suggested an association between light and myopia (Chapell et al, 2001;Czepita et al, 2003;Saw et al, 2002;Vannas et al, 2003), more importantly and recently, it has been demonstrated that myopes exposed to shorter sunlight hours (by 2.5 hours to 2.8 hours) as compared to non-myopes in the week in the young children (Dharani et al, 2012), though there was some degree of disagreement between different measure methods for sunlight exposure hours. However, other studies in earlier years did not report this association (Guggenheim et al, 2003;Saw et al, 2002;Zadnik et al, 2000).…”
Section: Sunlightmentioning
confidence: 99%